Hacktivism of the Anonymous Group as a Fighting Tool in the Context of Russia's War against Ukraine - Denys Svyrydenko; Wiktor Możgin (International Society of Philosophy and Cosmology, 2022)
The Russian invasion of the territory of the Ukrainian state in February 2022 disturbed the existing order in the world. The hybrid nature of this war resulted in the involvement of hacktivists from the Anonymous group. Therefore, the aim of this article is to analyze the legitimacy and legality of the hacking activities undertaken by members of the Anonymous group against the Russian state. Assuming that hacking activities are illegal in the light of the law, the author proves that during the war, this type of activity in cyberspace becomes justified and is one of the tools to fight the aggressor. At the same time, this fits in with the modern concept of hybrid wars because today's conflicts do not have the pure form of conventional actions, but are a mix of various fighting methods.